Literasi Matematis Siswa Madrasah Tsanawiyah dalam Memecahkan Masalah Fiqih Zakat - Pratiwi, Sabriyah Eka; Hartoyo, Agung; Mirza, Ade; Hamdani, Hamdani (JURNAL MathEdu (Mathematic Education Journal), 2024)
The purpose of this research is to describe the mathematical literacy level of Madrasah Tsanawiyah students in solving fiqih zakat problems and to see the consistency of the students' mathematical literacy level in solving zakat fitrah and zakat maal problems. This research used qualitative research approach with descriptive research method. The subjects in this research were 20 students who were in class VIII at MTs Darul Hidayah Rasau Jaya. Mathematical literacy test questions and interview guidelines were used as data collection instruments in this study. Based on the analysis of test results and interviews with students, it was found that students' mathematical literacy level was low. Students' mathematical literacy level in solving fiqih zakat problems is mostly at level 2 and there are no students who managed to reach level 5 and level 6. Students can interpret the given problem and solve it with the correct procedure. However, students still have difficulty finding different alternative ways to solve the problem and modeling. From the mathematical literacy test results with the context of zakat fitrah and zakat mal problems, not all students are consistent in achieving mathematical literacy levels.